2016
DOI: 10.15403/jgld.2014.1121.251.a2a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on Pegylated Interferon alpha 2a and First Generation Protease Inhibitor-based Antiviral Therapy in Naïve Patients Infected with Hepatitis C Virus Genotype 1

Abstract: Background & Aims: Smoking has multiple effects on factors influencing hepatitis C and antiviral therapy, including lipid metabolism, fibrosis, platelet count and adherence aspects. The aim of this analysis was to determine the impact of smoking on hepatitis C virus antiviral therapy. Methods: Data of two cohorts of an observational multicenter study including therapy-naïve patients infected with genotype 1 hepatitis C virus (HCV) treated with dual antiviral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…77,78 Approaches to address both will have multiple benefits to both patients and the health system and increases the likelihood that DAAs reduce morbidity and mortality rates better than delivering DAAs alone. 79 Tobacco smokers may face many challenges due to lack of access to care, poor adherence to therapy, and HCV reinfection due to risks such as injecting drug use. However, smokers living with HCV can be assisted to quit smoking with both pharmacotherapy and behavioural interventions where close monitoring of adherence and compliance to treatment is promoted.…”
Section: Discussionmentioning
confidence: 99%
“…77,78 Approaches to address both will have multiple benefits to both patients and the health system and increases the likelihood that DAAs reduce morbidity and mortality rates better than delivering DAAs alone. 79 Tobacco smokers may face many challenges due to lack of access to care, poor adherence to therapy, and HCV reinfection due to risks such as injecting drug use. However, smokers living with HCV can be assisted to quit smoking with both pharmacotherapy and behavioural interventions where close monitoring of adherence and compliance to treatment is promoted.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of smoking on MR and OS in patients with MPNs have not been investigated before, but in CML no effect of smoking on MR was observed in patients treated with imatinib 18 . However, in patients with hepatitis C treated with PEG‐IFN‐α2 and ribavirin, sustained viral response rates were lower in smokers compared with non‐smokers, and an in‐vitro study has shown down‐regulation of interferon receptors induced by smoking products 29,30 . Moreover, in patients with multiple sclerosis, smoking was associated with a reduced treatment response to PEG‐IFN‐β, possibly due to treatment‐induced neutralising antibodies 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent estimates indicate that 57%-67% of people with hepatitis C virus (HCV) smoke cigarettes (Basseri et al, 2010; Chew et al, 2015; Shuter et al, 2016; Zimmermann et al, 2016), 65%-73% consume alcohol (Drumright et al, 2011; North et al, 2014; Taylor, Denniston, Klevens, McKnight-Eily, & Jiles, 2016; Tsai, Ford, Li, & Zhao, 2012), and 57%-65% use illicit drugs (Sims et al, 2016; Whitehead, Hearn, Trenz, Burrell, & Latimer, 2014). Alcohol use and smoking independently accelerate progression to HCV-related liver disease and cancer (Jeng et al, 2009; Lok et al, 2009; Soeda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke contains several cytotoxic chemicals metabolized in the liver that cause chronic inflammation leading to cell death and contribute to viability and replication of HCV (Costiniuk et al, 2016; Zhao, Li, & Taylor, 2013). Alcohol use and smoking are independent risk factors for suboptimal HCV treatment outcomes (Choi, 2012; Zimmermann et al, 2016; Osna, Ganesan, & Kharbanda, 2015). Clinical guidelines recommend abstaining from alcohol, and several studies have advised clinicians to recommend smoking cessation for patients with HCV (Kertesz et al, 2014; Shuter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%